Quin Franciscan Friary, cloister, base - O'Donovan, Danielle; O'Donoghue, Aisling (My University, 2008)
Cloister base, from top down the moulding comprises roll, bell, hollow, plinth.
Cloister
Keywords: Architecture, Gothic -- Ireland; Quin Abbey; Architecture, Franciscan; Cloisters (Architecture); Late Medieval; roll moldings; plinth